High-throughput discovery of organic cages and catenanes using computational screening fused with robotic synthesis - R. L. Greenaway (Nature Portfolio, 2018)
Supramolecular assemblies remain of great importance to a variety of fields, yet their targeted design and synthesis remains highly challenging. Here, Cooper and colleagues combine computational screening with high-throughput robotic synthesis and discover 33 new organic cage molecules that form cleanly in one-pot syntheses.